Importancia de la educación intercultural en el proceso educativo del área de convivencia social de los niños de 4 años del centro de desarrollo infantil tía uchy de Guayaquil - Bravo Banguera, María Cristina (2016)
This research supports the importance of Intercultural Education and how to value the diversity in the classroom. Educating in intercultural attitudes allows children not to be discriminatory or exclusionary, it also favors a positive affective predisposition towards people of different cultures and providing them with the possibility of manifesting tolerant, respectful and supportive behaviors. This research work has a great impact at the social level, as it maintains a comprehensive attitude of diversity, as well as cultural and educational impact, since it enhances learning by sharing with other children about their customs or culture; To achieve a harmonious environment is prop osed within the objectives a proposal ad dressed to teachers with learning experiences where the child can participate in an exchange of knowledge with their peers…..